Injury risk among female soccer players in Zimbabwe - Risk Matiya (BMJ Publishing Group, 2023)
Background Women soccer is proving to be popular the world over and in African countries as well. However in spite of its popularity there is always the attendant high risk of injury. The risk of injury is associated with many factors which include personality factors and coping skills. Objective The purpose of the current study is to explore the relationship between personality traits, coping skills and risk of injury. Design The study was a retrospective cross sectional survey. Setting The study was carried out in Zimbabwe among women soccer players belonging to the elite division of the premier league. Patients (or Participants) All the participants were female soccer players whose age ranges were 18 through 35.200 participants were selected based on stratified random sampling from the national football association register. Interventions (or Assessment of Risk Factors) Four questionnaires were administered among 200 female soccer players in the current competitive season. The four questionnaires included the personality inventory questionnaire, B-COPE and the athletic injury questionnaire. Main Outcome Measurements A descriptive and inferential analysis was conducted examining the influence of personality traits and coping skills on injury frequency and severity. Results Descriptive and inferential analysis indicated that personality and coping skills were significant predictors of sporting injury among female soccer players, accounting for 30% of the variance. Conclusions The findings highlight the need to enhance prevention of athletes injuries by identifying athletes who are injury prone given their personality traits and coping styles. Athletes, coaches and sports medicine practitioners need to identify the role of stress, coping skills and personality in sport injuries, especially those relating to women's soccer.